2015
DOI: 10.1007/s00590-015-1711-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of postoperative results of balloon kyphoplasty (BKP) versus radiofrequency-targeted vertebral augmentation (RF-TVA): a prospective clinical study

Abstract: A certain superiority of RF-TVA with respect to pain relief, amount of cement required, savings of operating time and personnel, and greater safety with respect to cement leakage noted in this study are consistent with other published literature. The differences between the two methods in the frequency of subsequent postoperative fractures and the secondary loss of high restoration were encouraging regarding RF-TVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…With regard to pain reduction, the amount of cement required and the rate of cement leakages, the radiofrequency method would appear to be superior to balloon kyphoplasty in the treatment of vertebral body fractures [33]. For the treatment of insufficiency fractures of the sacrum, in our patients there is no significant difference in pain reduction, the amount of cement required or the rate of cement leakages, which was 0% for both BSP and RFS.…”
Section: Discussionmentioning
confidence: 54%
“…With regard to pain reduction, the amount of cement required and the rate of cement leakages, the radiofrequency method would appear to be superior to balloon kyphoplasty in the treatment of vertebral body fractures [33]. For the treatment of insufficiency fractures of the sacrum, in our patients there is no significant difference in pain reduction, the amount of cement required or the rate of cement leakages, which was 0% for both BSP and RFS.…”
Section: Discussionmentioning
confidence: 54%
“…There were 5 studies from Germany [8,9,24,26,27] and 1 study from USA. [25] The extracted studies included 2 RCTs, [9,24] 1 prospective cohort studies, [26] and 3 retrospective cohort studies. [8,25,27] Five studies were published in English while 1 was in German.…”
Section: Resultsmentioning
confidence: 99%
“…Two RCT studies [9,24] reported adequate randomization, but the allocation concealment and blinding during study were unclear, and the outcomes were not reported satisfactorily enough. The rest 4 studies [8,25–27] were not RCTs, and the randomization, concealment, blind, and outcome were of high risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoporotic vertebral fractures are a leading cause of disability among the elderly population. Their incidence in Europe has been estimated to be approximately 500.000 fractures per year rendering treatment options of particular importance [1][2][3][4] . While conservative management remains the mainstay of treatment, minimally invasive techniques such as kyphoplasty (KF) and vertebroplasty (VP) offer valuable alternatives, especially in cases of lasting pain.…”
Section: Introductionmentioning
confidence: 99%